AGS 위암세포주에서 Akt/mTOR 신호경로를 통한 영릉향 부탄올 분획물에서의 Apoptosis 유도 효과 - 이효재(Hyo Jae Lee); 서지원(Ji Won Seo); 김상현(Sang Hyeon Kim); 이창열(Chang Yeol Lee); 김상용(Sang Yong Kim); 김영민(Young Min Kim) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2022)
영릉향(Lysimachia foenum-graecum)은 두통, 치통, 염증 완화에 효과가 있는 한약재로 항산화, 항비만, 항염 효과가 있는 것으로 알려져 있다. 그러나 위암에서 영릉향의 항암 효과는 보고되지 않았으며, 본 연구에서는 AGS 인체 위암 세포에서 영릉향 부탄올 분획물(LFB)의 apoptosis 효과를 확인하고자 하였다. MTT assay를 통해 세포 증식 억제 효과를, Annexin V & Dead Cell staining을 통해 LFB의 apoptosis 유도 효과를 확인하였다. 또한, western blotting을 통해 LFB 처리가 농도 의존적으로 종양 형성과 암세포의 생존에 있어서 중요한 역할을 하는 p-Akt와 p-mTOR의 활성 수준을 감소시키는 것을 확인하였다. 더해서 LFB 처리가 농도 의존적으로 intrinsic pathway의 신호 단백질을 조절하여 apoptosis를 유도하는 것을 확인하였다. 그리고 caspase-3/7 activity assay를 통해 LFB가 농도 의존적으로 effecter caspase인 caspase-3의 발현을 증가시키는 것을 확인하였다. 마지막으로 LY294002(Akt inhibitor)와 rapamycin(mTOR inhibitor)을 처리하여 apoptosis 관련 신호 단백질의 발현 조절을 확인하였다. 그 결과 LFB가 Akt와 mTOR의 발현을 억제하여 이를 경유하는 signaling pathway를 통해 apoptosis를 유도하는 것을 확인하였다. Lysimachia foenum-graecum is a herbal plant known to be effective in relieving headaches, toothaches, and inflammation. It is known to have antioxidant, anti-obesity, and anti-inflammatory effects. However, anti-gastric cancer effects have so far not been reported. The purpose of this study was to investigate the apoptotic effects of the butanol fraction of Lysimachia foenum-graecum (LFB) in AGS human gastric cancer cells. The antiproliferative activity of LFB was confirmed by MTT analysis, and the apoptotic effect was confirmed by Annexin-V analysis. In addition, it was confirmed through western blotting that the LFB treatment reduced the expression levels of p-Akt and p-mTOR in a concentration-dependent manner. Akt plays a role in cell proliferation and migration of cancer cells by regulating important signaling factors such as mTOR and p53. mTOR induces the ubiquitination of p53 and plays an important role in tumorigenesis and the survival of cancer cells. This inhibition of Akt and mTOR leads to apoptosis by regulating the signaling molecules of the intrinsic pathway. In addition, LFB increases the expression level of the effector caspase, caspase-3, in a concentration-dependent manner. The expression of apoptosis-related signal proteins was confirmed by treatment with LY2940002 (Akt inhibitor) and rapamycin (mTOR inhibitor). These results indicate that LFB induces apoptosis through the endogenous pathway by suppressing the expression of Akt and mTOR. KCI Citation Count: 0